Analysis of the Implementation of E-Litigation with Artificial Intelligence Approach in Procedural Justice and Access to Justice in Pretrial Proceedings - Sitepu, Rida Ista; Alhuda Hasnda, Nuchraha (Perspektif Hukum, 2024)
The development of Artificial Intelligence in the current digital era across every sector of society has become a topic of discussion among legal experts for its potential application within the realm of justice systems. Consistency and time efficiency have become key considerations for implementation within the judicial system. Pre-trial proceedings in Indonesia are often seen as a secondary trial process, leading to inconsistencies in time, understanding of legislation, and document management, resulting in disadvantageous situations for the suspects. The integration of Artificial Intelligence in legal proceedings can enhance efficiency, accuracy, and ensure access to justice for suspects within the legal process. In the context of pre-trial proceedings, AI can be utilized to aid in data processing and analysis, decision-making, and monitoring compliance with principles of procedural justice. The research problem in this study revolves around two main questions: First, how does the legitimacy and legal certainty of utilizing electronic media within the Indonesian judicial system stand? Second, how can procedural justice and access to justice be implemented through the utilization of electronic media, particularly artificial intelligence, in pre-trial proceedings? This research is a doctrinal or normative study, relying on secondary data sources consisting of primary legal materials and qualitative data.